The Effect of Using Chemdroid (Chemistry on Android) Media on Students' Self-Efficacy in Thermochemistry Material - solikhin, febrian; Wijanarko, Andang (Universitas Negeri Surabaya, 2023)
This study aims to see the effect of using Chemdroid media on students’ self-efficacy in a thermochemistry topic. Chemdroid is Chemistry on Android. Self-efficacy is related to students’ beliefs in activities in the classroom. This type of research is quasi-experimental using post-test only control group design. In this study, two different classes were used which were declared to be normalyy distributed and homogeneous. The first class is the control class (CC-Class) which conducts conventional learning media as usual. The second class is the experimental class (EC-Class) which uses Chemdroid media for thermochemistry topic as a learning media in the classroom. Both classes have the same learning time, teacher and learning model. The instrument used in this study is a self-efficacy questionnaire that has been developed in previous studies but has been adapted to current research. The statement items used in this measuring instrument are 22 statements with 6 aspects. The test used is the Mann Whitney with the help os the SPSS program. The result of the analysis state that the significance is smaller than level of conficence. This proves that there is a significant difference with the use of Chemdroid media for a thermochemistry topic on the self-efficacy of the control class and experimental class students.